Techno-economic analysis of the transition toward the energy self-sufficiency community based on virtual power plant - Wang, Yafei; Gao, Weijun; Li, You; Qian, Fanyue; Yao, Wanxiang (Frontiers in Energy Research, 2023)
Distributed energy resources are important measures in increasing energy self-sufficiency and overcome global carbon reduction problem. However, the individual planned renewable energy generation poses a significant threat to the power grid. Therefore, virtual power plant (VPP) is attracting more and more attention as a means of aggregating distributed energy in urban areas. In this study, a VPP model consisted of updating high efficiency appliances, photovoltaic and energy storage systems was proposed. A comprehensive analysis for assessing the technical, economic and environmental benefits deriving from the VPP was presented, indicated the feasibility of a smart community to achieve power self-sufficiency with the support of the VPP. A smart community in Japan was selected as the research object, with a peak power demand of 57,350 kW. Analysis of the VPP’s load leveling performance, return on investment and CO2 emission reduction are performed. In addition, external factors such as electricity price changes and FiT policies are considered to assess the impact on the economics of the VPP. The results show that the introduction of the VPP system in the community can effectively stabilize the grid load with a peak shaving rate reaching up to 42.55% and improve the energy self-sufficiency rate of the region reached to 100%, while also providing superior economic and environmental benefits (16.26% CO2 emission reduction) on the demand side. Furthermore, the economic performance of VPP shows a good prospect with the fall of equipment price and the future trend of carbon tax growth. This paper provides important insights into the development of VPP at other countries, especially for low energy self-sufficiency regions.